Tool support for decision and usage knowledge in continuous software engineering - Kleebaum, Anja; Paech, Barbara (Software Engineering Workshops 2018, 2018)
In this paper, we present ideas and requirements for a tool support to manage decision and usage knowledge in continuous software engineering. As a first step, we introduce the JIRA DecDoc plug-in for documenting decision knowledge.